Understanding Thermostability Factors of Barley Limit Dextrinase by Molecular Dynamics Simulations - Du, Juan; Dong, Jianjun; Du, Songjie; Zhang, Kun; Yu, Junhong; Hu, Shumin; Yin, Hua (Frontiers in Molecular Biosciences, 2020)
Limit dextrinase (LD) is the only endogenous starch-debranching enzyme in barley (Hordeum vulgare Hv), which is the key factor affecting the production of a high degree of fermentation. Free LD will lose its activity in mashing process at high temperature in beer production. However, it is still lack of the understanding on the factor affecting the themostability of HvLD at atomic level. In this work, the molecular dynamics simulations were carried out for HvLD to explore the key factors affecting the thermal stability of limit dextrinase. The higher value of root mean square deviation (RMSD), radius of gyration (Rg), and surface accessibility (SASA) suggest that the instability of HvLD at high temperatures. Intra-protein hydrogen bonds, hydrogen bonds between protein and water decrease at high temperature. Long-lived hydrogen bonds, salt-bridges and hydrophobic contacts are lost at high temperature. The salt-bridge interaction analysis suggests that these salt-bridges are important for the thermostability of HvLD, including E568-R875, D317-R378, D803-R884, D457-R214, D468-R395, D456-R452, D399-R471, and D541-R542. Root mean square fluctuation (RMSF) analysis identified the thermal sensitive regions of HvLD, which will facilitate enzyme engineering of HvLD for enhanced themostability.